MnO2 coated multi-layer nanoplatform for enhanced sonodynamic therapy and MR imaging of breast cancer - Xu, Yan; Tan, Wanlin; Chen, Mingyu; Chen, Sijie; Tang, Kui; Liao, Haiqin; Niu, Chengcheng (Frontiers in Bioengineering and Biotechnology, 2022)
Sonodynamic therapy (SDT) is a promising new anti-tumor therapy that inhibits tumor growth by ultrasound activation of sonosensitizers to produce reactive oxygen species (ROS). However, the problems of hypoxia in the microenvironment within solid tumors and the effectiveness of SDT will decrease due to the little accumulation of sonosensitizers at the tumor site, as well as tumor cell tolerance, have limited the development of SDT. To overcome these problems, a core-shell structured nanoparticle (IR780/PLGA@MnO2 NPs) loaded with IR780 and manganese dioxide (MnO2) was developed as a nanocarrier to transport the sonosensitizer IR780 and the generated oxygen into the tumor tissue. The MnO2 shell layer of IR780/PLGA@MnO2 NPs can prevent the premature release of IR780 in the blood and also it can react with acidic and high H2O2, the generated oxygen can relieve tumor tissue hypoxia, and the generated Mn can enhance magnetic resonance imaging (MRI) signal intensity by acting as a contrast agent for MRI. More importantly, the released IR780 can produce ROS to kill tumor cells under ultrasound excitation. This PH-responsive and H2O2-triggered SDT based on the IR780/PLGA@MnO2NPs is an effective platform to inhibit tumor growth with negligible systemic toxicity. This work develops a multifunctional therapeutic integrated nanoplatform for breast cancer treatment, which is expected to be used in the clinic.